Studies on the Influence of Residual Stresses on the Fatigue Life of Rolling Bearings in Dependence on the Production Processes - Pape, Florian; Coors, Timm; Poll, Gerhard (Frontiers in Mechanical Engineering, 2020)
The production process significantly influences the surface properties of rolling element bearings raceways. Deep rolling can induce a depth dependent residual stress state. Previous numerical and experimental studies have shown that rolling bearings fatigue life can be positively influenced by high compressive residual stress to a depth of around 300 µm from the surface. By extending the components life, the resource efficiency of machine components can be increased. In order to determine the influence of the residual stress state in bearing fatigue life, a calculation method was developed for predicting the bearing fatigue life. This method was validated for hard-turning and subsequent deep rolling by experiments on a test rig in four-bearing configuration under radial load. An increase of the L10 bearing life by a factor of 2.5 has been achieved by inducing residual stresses on the bearing’s inner ring. Due to similar process control, the manufacturing steps turning and deep rolling were combined. Bearings were manufactured combining the processes hard-turning and deep rolling (called turn-rolling). The heat from the hard machining has an effect on the residual stresses in the bearing subsurface, thus further altering the magnitude and maximum depth of the residual stress influencing the microstructure. With these bearings, the additional fatigue life was determined experimentally and compared to the results of the bearings produced by hard-turning and subsequent deep rolling. It could be shown, that the process of hard turning and subsequent deep rolling has highest potential to achieve improved bearing fatigue life. These findings were transferred to a “Tailored Forming” shaft with integrated raceway in a second step. In this case, a shaft made of mild steel is combined with a cladding layer of high strength bearing steel to be used as a bearing raceway.